Pengaruh Pendidikan Kesehatan Berbasis Kearifan Lokal Terhadap Pencegahan Anemia dan Peningkatan Body Image Remaja Putri di Kabupaten Langkat - Srinur Nilawati; Sapnita Sapnita (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Anemia among adolescent girls remains a major public health problem in Indonesia because it adversely affects growth, learning ability, productivity, reproductive health, and increases the risk of pregnancy-related complications in later life. In addition, many adolescent girls experience negative body image due to the influence of social media and unrealistic beauty standards. Health education has predominantly relied on conventional information delivery methods and has rarely integrated local wisdom as a learning approach. However, Langkat Regency possesses rich Malay cultural values and abundant local food resources that can be utilized to enhance the effectiveness of health education. Several local food-based educational programs have demonstrated improvements in knowledge related to anemia prevention, indicating that a local wisdom-based approach deserves further development. Objective: This study aimed to analyze the effect of local wisdom-based health education on anemia prevention and the improvement of positive body image among adolescent girls in Langkat Regency. Methods: This study employed a quasi-experimental design with a pretest–posttest control group design. The intervention group received local wisdom-based health education for four weeks, while the control group received conventional health education. The measured variables included knowledge of anemia, anemia prevention behaviors, adherence to iron and folic acid supplementation, and body image. Expected Results: Local wisdom-based health education is expected to significantly improve knowledge of anemia, anemia prevention behaviors, adherence to iron and folic acid supplementation, and positive body image compared with conventional health education. Conclusion: The integration of local cultural values into health education is expected to serve as an effective health promotion model for improving the health status of adolescent girls while simultaneously preserving local cultural heritage.